Diagnosis Cepat Kandidemia Neonatus dengan Pemeriksaan Spesimen Darah Pulasan Giemsa - Ridhawati Ridhawati; Riva Ambardina Pradita; Mulyati Mulyati; Robiatul Adawiyah (Jurnal Ilmu Kedokteran, 2019)
Candidemia is one of the major problems in neonates with low birth weight (LBW). Neonatal candidemia has a high rate of morbidity and mortality. Early initiation of antifungal therapy could be decreasing the mortality, but this management often hampered due to late diagnosis. The gold standard for diagnosing candidemia is blood culture, but it takes a long time about 5 days. A rapid alternative method is needed to decrease candidemia morbidity and mortality. The method chosen in this study is Giemsa stain of blood smear which result could be read within one hour. The study was conducted in the Department of Parasitology, Faculty of Medicine Universitas Indonesia with a total blood samples of 170 from 2009-2012. Blood samples are devided in two, first is made thick blood smear than stain with giemsa, than read by microscope by 400×and 1000× magnification. The second is cultured on Sabauraud agar media and incubated in room temperature for ten days. Thirty four patients (20%) were positive for Candida, 28 (82.4%) positive samples with both giemsa staining and culture, while 6 (17,6%) positive culture samples but negative giemsa staining. The values of the sensitivity and specificity of the Giemsa stained blood smear examination were 82%, and 100%. This result shows that Giemsa staining has a good diagnostic value for detecting neonatal candidemia.